A Brief Analysis of the Working Load and Stroke of the Linear Actuator for the Passenger Aircraft Cargo Door. Issue 1 (1st December 2022) - Wang, Xiaolu; Wang, Danyang; Guo, Peng; Niu, Guangran; Liu, Ruijun; Guo, Yucheng
Abstract : Towards the cargo door actuator of the passenger aircraft, the load type during service is analyzed, and the load profile is identified and illustrated. For the door actuation system composed of a rear support beam, linear actuator, door, etc., the theoretical working load and stroke of the actuator are calculated, as well as the load and stroke when the components are elastomers. The comparison results show that the reduction of the door stiffness will increase the actuator load, and the reduction of the rear support beam and actuator stiffness will increase the stroke. This study can provide a reference for engineering problems such as door system stiffness allocation, door opening stroke design, and evaluation.